Pendidikan Karakter Humanisme: Mewujudkan Pendidikan Berkualitas Di Tengah Ancaman Dehumanisasi Oleh Artificial Intelligence - Dehya Al fathurizqiyah; Sujarwo Sujarwo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The advancement of Artificial Intelligence (AI) in education has brought significant transformation alongside a serious threat of dehumanization, namely the erosion of human values such as empathy, social interaction, and pedagogical relationships in the learning process. This study aims to analyze the role of humanistic character education in realizing quality education amid the threat of AI-driven dehumanization. The research employs a qualitative approach using a literature review technique through the examination of relevant, credible, and up-to-date scientific literature. The findings reveal that AI has the potential to create digital heteronomy that undermines students' learning autonomy and triggers a decline in character and morality, thereby hindering the achievement of quality education in accordance with SDGs 2030. Humanistic character education emerges as a solution that positions students as whole individuals to be developed cognitively, affectively, morally, and spiritually through a teacher-AI collaboration model grounded in Pancasila values. Its implementation requires an integrated strategy involving national policy, the role of teachers as facilitators and moral guides, as well as the active involvement of families and communities. This research implies the importance of balancing technological advancement with the strengthening of human values so that education can continue to produce generations that are intellectually competent, emotionally mature, and morally resilient.